A study of the factors affecting mobile money penetration rates in the West African Economic and Monetary Union (WAEMU) compared with East Africa - Sionfou Seydou Coulibaly (Financial Innovation, 2021)
According to the 2017 Global Financial Inclusion (Global Findex) database, the average penetration rate of mobile money accounts in East Africa is higher than that of the WAEMU. This study attempts to understand the factors driving the adoption and the use of mobile financial services in the WAEMU compared to East Africa. To achieve this, micro-level data from the 2017 Global Findex database are used to perform probit and multinomial logit estimations. The findings reveal that the same determinants influence the adoption and use of mobile money accounts across the populations of both groups of countries, specifically those related to the least vulnerable social categories (i.e., males, older, more educated, richer and part of the workforce). Therefore, in comparison to East Africa, the delay in the penetration of mobile money accounts observed in the WAEMU may be attributed to insufficient policies for increasing the awareness of the benefits of mobile financial services. The study recommends that governments in WAEMU countries promote the use of mobile money accounts among the working-age population (adults aged between 25 and 64) through the improvement of individual income level, and the introduction of incentives into the education system to encourage their population to attain higher levels of education.
Keywords: G21; C33; C34; C35; R10; 650; East Africa; Financial inclusion; Mobile money; Multinomial logit; Probit; WAEMU